Dynamic Simulation and Visualisation of Fermentation: Effect of Process Conditions on Beer Quality. Issue 7 (2016) - Rodman, Alistair D.; Gerogiorgis, Dimitrios I.
Abstract: Fermentation is the central, most important unit operation in alcoholic beverage manufacturing and has already been studied by means of first-principles dynamic models, which explicitly consider the temperature effects and employ parameterisations obtained using industrial beer brewing campaign data. Nevertheless, the precise effect of initial conditions on beer quality and flavour has not been documented. Multi-objective optimisation encompasses ethyl alcohol maximization and batch duration minimisation, but must also quantitatively monitor all the critical flavour components (Rodman & Gerogiorgis, 2016). Dynamic simulation and visualisation of the key (ethyl alcohol, ethyl acetate, diacetyls) concentrations is pursued for varying initial condition (sugar concentration, pitching rate, active yeast fraction) parameters, and hundreds of thousands of possible temperature manipulation profiles over the entire brewing horizon. Feed sugar content is confirmed to govern attainable alcohol concentration, but our notable finding is that pitching rate is a very efficient manipulation, in contrast to the weak effect of initial active yeast fraction.